Move over, men! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Navy Simukonda, Acting Director of the Transkei Land Service Organisation (TRALSO) in Umtata, Eastern Cape, in South Africa has passed on to us the success story of the Masibambane Women s Project in Mpindweni near Umtata.'The project started in...